Anti-neoplastic effects of the antipsychotic drug penfluridol in preclinical prostate cancer models - van de Merbel, Arjanneke F.; van der Mark, Maaike H.; Aalders, Tilly; Puhr, Martin; Mehra, Niven; Schalken, Jack; van der Horst, Geertje; van der Pluijm, Gabri (Frontiers in Oncology, 2025)
IntroductionThe development of therapy resistance and the formation of distant metastases represent clinical unmet needs for patients with advanced prostate cancer (PCa). The use of drugs for other indications, i.e. drug repurposing, shows great promise for cancer treatment. Drug repurposing could allow new cancer treatments to be introduced relatively quickly and at lower costs. Penfluridol, an approved antipsychotic drug, has strong cytolytic effects in multiple cancers.MethodsIn this study, we have investigated the potential anti-tumor effects of penfluridol in preclinical and ‘near-patient’ PCa models.ResultsPenfluridol significantly reduced the viability of a panel of human PCa cells, induced apoptosis by increasing caspase-3/7 levels and decreased the number of PCa stem cells in vitro. Penfluridol reduced the viability and induced cytotoxic effects in three-dimensional cultures and in ex vivo cultured PCa tissue slices (patient-derived xenograft, freshly isolated PCa biopsies). Moreover, penfluridol significantly reduced the viability of docetaxel-resistant PCa cells and exerted synergistic effects in combination with docetaxel in docetaxel-resistant PCa.DiscussionIn conclusion, penfluridol exhibited cytotoxic effects in multiple preclinical PCa models. Further research is warranted to address the translational value of our findings.